BENTUK DAN KELIMPAHAN MIKROPLASTIK DI PERAIRAN PULAU PASARAN, BANDAR LAMPUNG - Tri Banowati, Nurmaya; Hasani, Qadar; Mayaguezz, Henky; Delis, Putu Chintia (Jurnal Perikanan Unram, 2025)
Microplastics are plastic particles formed from plastic degradation to a size of <5 mm. Microplastics in waters can have adverse effects on marine organisms, aquatic ecosystems, and humans. This study aims to determine the shape, size, color, abundance, and distribution of microplastics and to determine the relationship between water quality and the abundance of microplastics in the waters of Pasaran Island. The study was conducted in November-December 2022 in the waters of Pasaran Island. Preparation and identification of microplastics in water samples were carried out in the following stages: sample preparation, organic material degradation, density separation, sample sorting, and observation of microplastic types. Data analysis was carried out using the principle component analysis (PCA) method using the Statistical Program for Social Science (SPSS) version 24 with physical and chemical parameters of the waters. Based on the study, 4 forms of microplastics were obtained, namely fiber, fragments, films, and pellets. The form of microplastic that dominated the four stations was the fiber form at 45.1%. The highest abundance of microplastics was at Station 2 (mangrove ecosystem) at 22.63 particles/liter. PCA analysis showed that the abundance of microplastics in the form of fibers, fragments, films, and pellets was negatively related to pH, salinity, current, temperature, and brightness. Increasing public awareness in reducing the use of single-use plastics and managing plastic waste needs to be done to reduce the abundance of microplastics in the waters of Pasaran Island.